2011
DOI: 10.1161/circoutcomes.110.959809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inadequate Blood Pressure Control Among Veterans After Acute Ischemic Stroke Hospitalization

Abstract: Background Reducing blood pressure (BP) after stroke reduces risk for recurrent events. Our aim was to describe hypertension care among veterans with ischemic stroke including BP control by discharge and over the 6 months post stroke event. Methods and Results The Office of Quality and Performance Stroke Special Study included a systematic sample of veterans hospitalized for ischemic stroke in 2007. We examined BP control (<140/90 mmHg) at discharge excluding those who died, enrolled in hospice, or had unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…At particular risk are those with resistant hypertension or black patients who are both more likely to be uncontrolled in the post stroke period, and may not have their medications changed or titrated. 8, 23 The lack of treatment intensification which we report are similar to those reported by Heisler et al 11 These investigators studied 38, 327 Veterans with hypertension; treatment intensification occurred at 30% of 68,610 elevated BP visits. While we observed higher proportion of intensifications (58-65%), these investigators also found no relationship between intensification and medication adherence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At particular risk are those with resistant hypertension or black patients who are both more likely to be uncontrolled in the post stroke period, and may not have their medications changed or titrated. 8, 23 The lack of treatment intensification which we report are similar to those reported by Heisler et al 11 These investigators studied 38, 327 Veterans with hypertension; treatment intensification occurred at 30% of 68,610 elevated BP visits. While we observed higher proportion of intensifications (58-65%), these investigators also found no relationship between intensification and medication adherence.…”
Section: Discussionsupporting
confidence: 88%
“…6-8 A systematic sample of 5000 records that included all ischemic stroke patients at hospitals with less than 55 stroke hospitalizations and an 80% random sample of patients at hospitals with more than 55 stroke hospitalizations were selected for abstraction. Because of this sampling, the number of patients per hospital ranged from 1 to 198 (mean=38 and standard deviation [SD] =28).…”
Section: Methodsmentioning
confidence: 99%
“…However, the results of this study show those patients with elevated BP at the time of discharge from an ischemic stroke hospitalization continue with poorly controlled BP in the year post‐discharge. These findings are similar to a previous retrospective study conducted in 2054 stroke patients, seen within a 6‐month period from their index event, among which 673 (32.8%) remained with uncontrolled BP …”
Section: Discussionsupporting
confidence: 90%
“…However, our study setting closely resembles the United Kingdom National Health Service and integrated managed care organizations in the United States, and the clinical profiles of our participants were similar to recent reports of stroke survivors from other Canadian provinces, the US, the UK and Europe. 1,2,10,20,24,25,28 When considering the external validity of our results, the under-treatment of vascular risk factors is a nearly universal phenomenon and has been documented in many other settings and for other atherosclerotic conditions.…”
Section: Secondary Outcomesmentioning
confidence: 77%